2022
DOI: 10.1111/emr.12569
|View full text |Cite
|
Sign up to set email alerts
|

Managing vertebrate pest Sambar Deer at low abundance in mountains

Abstract: Summary Invasive species such as vertebrate herbivores cause threats to native ecosystems through causing changes to vegetation composition and structure, competition, ecosystem engineering, impacts on soil, and through spreading disease. In the mountainous country of Australia, Sambar Deer (Rusa unicolor) are becoming an increasing threat to fragile and endangered ecosystems, which are also facing other significant threats such as climate change. Methods for ameliorating these impacts are currently limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Aerial culling can be an effective, rapid, and humane means for removing large numbers of alien deer (Husheer and Robertson 2005;Bengsen et al 2022;Pulsford et al 2023), alien pigs (Cox et al 2022;Hamnett et al 2023), and other pest species in vast, remote, and inaccessible landscapes. In 2020, 2021, and 2022, South Australia's aerial culling programs have removed approximately 3,000 alien deer per year (BDO Econ-Search 2022).…”
Section: Aerial Cullingmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerial culling can be an effective, rapid, and humane means for removing large numbers of alien deer (Husheer and Robertson 2005;Bengsen et al 2022;Pulsford et al 2023), alien pigs (Cox et al 2022;Hamnett et al 2023), and other pest species in vast, remote, and inaccessible landscapes. In 2020, 2021, and 2022, South Australia's aerial culling programs have removed approximately 3,000 alien deer per year (BDO Econ-Search 2022).…”
Section: Aerial Cullingmentioning
confidence: 99%
“…Program costs and efficiency will vary with location and density of deer. For example, the cost of targeting sambar deer at low densities in alpine environments exceeded $1,000 deer -1 (Pulsford et al 2023). We compared 11 aerial culling programs that varied in location, planning, staffing, and logistic requirements.…”
Section: Cost Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting new technologies could enhance the efficiency of aerial programs and welfare outcomes for target animals. Recently, Pulsford et al (2023) concluded that thermal-assisted aerial culls were more effective than ground shooting when targeting sambar deer, and demonstrated improvements in both efficiency and welfare outcomes for fallow deer by incorporating thermal technology into their aerial programs. Government programs across Australia are trialling new combinations of firearms for different terrain and species of deer to improve the efficiency of culling operations.…”
Section: Introductionmentioning
confidence: 99%
“…P3, P4, and P5 are separate components of a large program. All costs in AU$ and include goods and services tax.Aerial culling can be an effective, rapid, and humane means for removing large numbers of feral deer(Bengsen et al 2022;Husheer and Robertson 2005;Pulsford et al 2023), feral pigs(Cox et al 2022), and other pest species in vast, remote, and inaccessible landscapes. Over the last three years, South Australia's aerial culling programs have removed approximately 3,000 feral deer per year (BDO EconSearch 2022).…”
mentioning
confidence: 99%